Non-Surgical Management of Traumatic Non-penetrating Hyphaema among Nigerian Ophthalmologists - Chidi Fidelis, Okosa Michael Chuka, Onyekwe Lawrence Obizoba,Anajekwu Cosmas Chinedu Mbakigwe (Pakistan Journal of Ophthalmology, 2018)
Purpose: To explore non-surgical treatment preferences and practices of ophthalmologists in Nigeria. Material And Methods: The study was a survey done by means of selfadministered semi-structured questionnaire to Nigerian ophthalmologists. Literature search was done using Google, and HINARI . Results: In-patient treatment is favored by 72%; bed rest is practiced by 97.2%; while 54.8% routinely pad traumatized eye. Commonest medications used are glucocorticoids by 87.1%; cycloplegics by 80.6%, and oral carbonic anhydrase inhibitors 59.1%. The commonest combinations of drugs used are these three medications, being deployed by 50.5% of surveyed ophthalmologists routinely in all patients with closed globe traumatic hyphaema. Except for CAI no oral medications enjoys significant favor. Conclusion: No aspect of treatment enjoys universal agreement. Majority advocates routine use of topical glucocorticoid and cycloplegic agents. Bed rest, hospitalization and padding should not be routine but based on need. These are suggested as approach for management of this condition pending availability of a better guideline.